2010 Conference Proceedings IPEC 2010
DOI: 10.1109/ipecon.2010.5697027
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies above the harmonic range - challenge of the future?

Abstract: During the last two decades, the main topic in respect to power quality (beside voltage dips and outages) was and still is harmonic distortion. However, following the development in power electronics with an increasing use of self-commutated converters, problems are shifting slowly to higher frequencies. Voltages with frequencies above the "classical" harmonic range create new challenges and require new solutions. With the largescale introduction of electric vehicles, solar power, wind turbines or similar appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
5
0
3
Order By: Relevance
“…The ESR model of an electrolytic capacitor is shown in Figure 5 [8,11], where the resistance 0 R accounts for the sum of resistances of foil, tabs, and terminals, 1 R represents the electrolyte resistance, 1 C represents the terminal capacitance, and the parallel combination of 2 R and 2 C represents the dielectric losses. According to Figure 5, the complex impedance of the capacitor is described as…”
Section: Capacitor Models and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ESR model of an electrolytic capacitor is shown in Figure 5 [8,11], where the resistance 0 R accounts for the sum of resistances of foil, tabs, and terminals, 1 R represents the electrolyte resistance, 1 C represents the terminal capacitance, and the parallel combination of 2 R and 2 C represents the dielectric losses. According to Figure 5, the complex impedance of the capacitor is described as…”
Section: Capacitor Models and Characteristicsmentioning
confidence: 99%
“…The high-frequency harmonic distortion of the current and voltage waveforms in PWM converters is produced by the voltage-source inverter using fast electronic switches which are commutated with very high rate of voltage rise (up to 50 kV/μs) and pulse repetition frequency (about 10-50 kHz) [1,2]. As an example, Figures 1 and 2 present the distorted current and voltage waveforms generated by LS800-42K2-TD frequency converter with dc-link and registered by digital oscilloscope during laboratory measurements [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through this supraharmonic distortion, malfunctions or impairments of household devices (LED lamps, mobile phone chargers, laptop power supplies etc.) increasingly occur [1] [2]. Furthermore, already implemented measurements and simulations have shown that supraharmonic disturbances are basically a local phenomenon because of the interaction between multiple devices and the interaction of the devices with the low voltage grid.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, more and more power electronic components are used for the efficiency enhancement in electric devices. The increasing amount of these high frequency switching techniques like photovoltaic (PV) inverters or active power factor correction (PFC) circuits in switched-mode power supplies with typical switching frequencies above 2 kHz cause increasing HF emissions in the frequency range of 2 kHz to 150 kHz [1] [2]. Therefore, the influence of these HF disturbances on electronic mass-market products like LED lamps have to be investigated in more detail.…”
Section: Introductionmentioning
confidence: 99%